E-172 Hypercoagulability and endovascular management of idiopathic intracranial hypertension. (22nd July 2018) - Cho, S; Chung, C; Luciano, M; Moghekar, A; Xu, R; Rao, A; Martinez, M; Geocadin, R; Hui, F
Abstract : Background: Endovascular management of idiopathic intracranial hypertension is an increasingly employed treatment option. The venous pathology that results in venous hypertension is heterogenous, and may arise from extrinsic compression, arachnoid granulations, masses or endovenous thrombi, partial or complete. The precise mechanism through which venous hypertension leads to cerebral spinal fluid hypertension remains unclear, but may result from the so-called glymphatic system. This system, which is aquaporin 4 mediated, is thought to allow interchange of cerebral spinal fluid with intracellular material, and back to the vascular space. Treatment of venous stenoses with endovenous stents has been performed to diminish intracranial hypertension, without explicit regard for etiology. The role and management of hypercoagulable states with respect to endovascular treatment of idiopathic intracranial hypertension has yet to be fully explored, but is certainly a theoretical concern due to the potential for thrombotic events to be both a cause for hypertension, and a complication post therapy given the presence of a stent. Methods: The CSF Disorder database was retrospectively queried to identify patients with clinically identified idiopathic intracranial hypertension and concomitant hypercoagulability. Clinical data was reviewed, with accompanying demographic information, clinical and interventional management as well as outcomes and complications. Results: Five patients were identified: Three were male, one of which had developed a dural fistula in addition to bilateral venous sinus occlusion. Another patient had unilateral venous sinus occlusion. The third had presented with pulmonary embolism with no other venous thrombi except for the right venous sinus occlusion which had improved since anticoagulation. These three patients all had known hypercoagulability prior to venous pressure monitoring. Of the two female patients, both presented with venous sinus stenosis with idiopathic intracranial hypertension. One of the patients had a relatively rigid venous sinus narrowing which required both stent and balloon angioplasty which prompted testing for hypercoagulability. The other had stent placement and angioplasty complicated several weeks later with stent thrombosis which prompted testing for hypercoagulability. Conclusions: The database queried had a total of 46 patients, of which 5 had hypercoagulability. The overall incidence of hypercoagulability in idiopathic intracranial hypertension is not well defined, but in this series is as low as 10.8%, but may underestimate the incidence as this is not routinely tested. Given the occurrence of stent thrombosis in one such patient, the potential risks in patients undergoing stenting for intracranial hypertension should be considered carefully. Whether dual antiplatelet therapy or anticoagulation should be employed in venous sinus stenting remains unstudied, especially in patients with hypercoagulability. Disclosures: S. Cho: None. C. Chung: None. M. Luciano: None. A. Moghekar: None. R. Xu: None. A. Rao: None. M. Martinez: None. R. Geocadin: None. F. Hui: None.